Impact of Cryptocurrency Mining on the Power Sector of Irkutsk Oblast: A Techno-Economic Assessment and Regulatory Measures - Popova , Ekaterina V.; Tomin , Nikita V. (Economy of Regions, 2026)
The development of industrial scale cryptocurrency mining in Irkutsk Oblast (Russia) has become a key driver of the growth in electricity demand, creating both economic opportunities and significant challenges for the region’s energy infrastructure. The region was selected for the study due to its unique conditions, including some of the lowest electricity tariffs in Russia, increased consumption limits during the winter heating season, and substantial unused generation capacity in the northern part of the region. These factors make it an attractive hub for miners. This study provides a techno-economic assessment of mining development in the region and proposes measures for its sustainable regulation. It analyses the current state of mining and evaluates its impact on the regional power sector and economy. The analysis is based on aggregated and anonymized data from local energy companies, as well as relevant scientific and expert materials at the regional level. The results of the multiplicative analysis indicate the need for a balanced approach that supports legal mining, which is projected to reach up to 500 MW by 2038, while protecting energy infrastructure and consumers. The estimated regional multiplier (K = 1.22) suggests that one ruble of localized autonomous spending from legal and semi-legal mining has a moderate positive effect on gross regional product. The study also shows that positive economic outcomes are achieved when the share of legal mining exceeds 60 %. The proposed measures include differentiated tariffs, microgrids based on renewable energy, and the involvement of miners in load management. These measures can reduce peak demand and generate economic benefits of up to 4.9 billion rubles annually, thereby increasing regional revenues and supporting technological development.